FOSTERING ETHICAL BEHAVIOR: UNVEILING THE INTERPLAY OF ETHICAL WORK CLIMATE, TRANSPARENT COMMUNICATION, AND PERSON-ORGANIZATION FIT - Amelia, Syifa Nurayini; Sari, Santi Retno (Cirebon International Conference on Education and Economics Proceeding, 2024)
Recently, there has been a lot of unethical behavior in the world of work. Such as disclosures, acts of corruption, insulting officials, and even the widespread use of harsh and unethical language in the world of work. Therefore, this research proposes a mechanism model that influences ethical behavior in the world of work specifically in the ministry of agriculture environment. The research objective is to examine the influence of an ethical work climate on ethical behavior which is mediated by the formation of transparent communication and strengthened by the existence of person-organization fit. The method used to test this is using PROCESS V.3.5. This analysis technique was chosen because of PROCESS's strength in testing models that contain mediation and moderation by producing a mediation moderation index, as well as the ability to display moderation graphs. The respondents sampled in this research were 122 employees. Employees from various sectors, because sampling uses chain referral sampling which rolls from one respondent to another. The results show that an ethical work climate influences ethical behavior mediated by transparent communication. Furthermore, the better suited employees are to the organization, the stronger the influence of transparent communication on ethical behavior. This language provides benefits by providing insight into the need to organize a work climate that displays ethics, so that employees will be more accustomed to behaving ethically. And the need to promote open communication. Apart from that, organizational harmony with actors or employees also has a role in strengthening the formation of ethical behavior.